Treatment Sequencing and Outcome of Chronic Lymphocytic Leukemia Patients Treated at Fondazione Policlinico Universitario Agostino Gemelli IRCCS: A Thirty-Year Single-Center Experience - Innocenti, Idanna; Fresa, Alberto; Tomasso, Annamaria; Tarnani, Michela; De Padua, Laura; Benintende, Giulia; Pasquale, Raffaella; Galli, Eugenio; Morelli, Francesca; Giannarelli, Diana; Autore, Francesco; Laurenti, Luca (Cancers, 2023)
Background: This monocentric retrospective study describes the treatment patterns and outcomes of chronic lymphocytic leukemia (CLL) patients. Methods: Adult CLL patients treated between 1992 and 2022 were included. The time to next treatment (TTNT) was defined as the time from the treatment’s start to the start of a subsequent therapy or death. The time to next treatment failure or death (TTNTF) was defined as the time from treatment discontinuation to the discontinuation of a subsequent therapy or death. Results: Of 637 registered patients, 318 (49.9%) received treatment. We evaluated 157 cBTKi-exposed, 34 BCL2i-exposed cBTKi-naïve, and 26 double-exposed patients. The five-year TTNT values in the cBTKi-exposed patients were 80% (median NR), 40% (median 40 months), and 21% (median 24 months) months in the first line (1L), second line (2L), and beyond the second line (>2L), respectively (p < 0.0001). The five-year TTNT values in the BCL2i-exposed patients were 83% (median NR), 72% (median NR), 12% (median 28 months) in the 1L, 2L, and >2L, respectively (p = 0.185). The median TTNTF was 9 months (range 1–87) after cBTKi and 17 months (range 8–49) after both a cBTKi and BCL2i. Conclusions: This study suggests that, in CLL patients, the earlier we used targeted therapies, the better was the outcome obtained. Nonetheless, the poor outcomes in the advanced lines of therapy highlight the need for more effective treatments.
CRIS-Team Scopus Importer:2023-12-22
Keywords: chronic lymphocytic leukemia; personalized medicine; targeted therapy